1999
DOI: 10.1128/mcb.19.7.5143
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-Activated Protein Kinase Kinase Kinase 1 Activates Androgen Receptor-Dependent Transcription and Apoptosis in Prostate Cancer

Abstract: Mitogen-activated protein (MAP) kinases phosphorylate the estrogen receptor and activate transcription from estrogen receptor-regulated genes. Here we examine potential interactions between the MAP kinase cascade and androgen receptor-mediated gene regulation. Specifically, we have studied the biological effects of mitogen-activated protein kinase kinase kinase 1 (MEKK1) expression in prostate cancer cells. Our findings demonstrate that expression of constitutively active MEKK1 induces apoptosis in androgen re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
127
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(134 citation statements)
references
References 56 publications
(78 reference statements)
6
127
0
1
Order By: Relevance
“…This is consistent with previous ®ndings of inverse correlation between JNK inhibitory phosphatase MKP-1 levels and apoptosis in prostate cancer tissue samples (Magi-Galluzzi et al, 1997, and recent ®ndings which implicate the MAPKKK in apoptosis of androgen sensitive prostate cancer cells (Abreu-Martin et al, 1999); altogether, these results suggest that JNK activation has a role in prostate cancer. If so, JNK can be used as a target for developing treatment modalities in androgen dependent and sensitive prostate cancer, as well as in the advanced disease.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with previous ®ndings of inverse correlation between JNK inhibitory phosphatase MKP-1 levels and apoptosis in prostate cancer tissue samples (Magi-Galluzzi et al, 1997, and recent ®ndings which implicate the MAPKKK in apoptosis of androgen sensitive prostate cancer cells (Abreu-Martin et al, 1999); altogether, these results suggest that JNK activation has a role in prostate cancer. If so, JNK can be used as a target for developing treatment modalities in androgen dependent and sensitive prostate cancer, as well as in the advanced disease.…”
Section: Discussionsupporting
confidence: 93%
“…These results therefore indicate that the restoration of expression of androgen-repressed transcripts is a systematic feature of recurrent prostate cancers. This provides unbiased, genomic-level support to the hypothesis that the reactivation of androgen-responsive genes in the absence of a ligand is involved in the growth of androgen-independent tumors (Culig et al, 1994;Gregory et al, 1998;Craft and Sawyers, 1998;Craft et al, 1999;Abreu-Martin et al, 1999;Peterziel et al, 1999). The gene expression pro®les do not indicate at which level of androgen regulation this reactivation takes place and what the speci®c molecular mechanisms may be.…”
mentioning
confidence: 83%
“…Other reports also suggested that mitogen-activated protein kinase kinase kinase 1 may induce prostate cell apoptosis via the induction of AR transactivation (28) and that addition of 10 nM DHT to PC-3 cells transfected with AR will accelerate the cell apoptosis (24). As BRCA1 is an integral component of the RNA polymerase II holoenzyme (44), it is possible that androgen-AR may need BRCA1 to communicate properly with RNA polymerase II for the transactivation of some AR target genes related to cell growth arrest, death, or proliferation.…”
Section: Mutations Of Brca1 Reduce the Enhancement Of Ar Transactivatmentioning
confidence: 97%
“…In addition, androgen can inhibit the growth of LNCaP-derived cells, which grow under androgen ablation condition for over 40 passages (26,27). Moreover, mitogen-activated protein kinase kinase kinase 1 may induce prostate cell apoptosis via the induction of AR transactivation (28). Thus, it has been well documented that androgen and AR may play important roles both in cell growth and apoptosis; the detailed mechanisms of how androgen and AR signaling can play these two opposite functions, however, need further characterization.…”
mentioning
confidence: 99%